Total reflection membrane that corrosion resistant photovoltaic module used - WANG TONGXIN; XUE QUNSHAN; YIN LEICHENG; SHEN YICHUN; XU XIANHUA (2018)
The utility model relates to a total reflection membrane that corrosion resistant photovoltaic module used is applied to photovoltaic field. A total reflection membrane that corrosion resistant photovoltaic module used includes tie coat, stratum basale, structural layer, reflector layer and protective layer. The tie coat is the bottom, and the tie coat is used for welding the band region territoryto photovoltaic module this total reflection membrane is fixed. The stratum basale sets up in the tie coat top for the bearing structure layer. The structural layer sets up on stratum basale upper portion, and the structural layer includes base and the micro -structure that is located a plurality of parallel arrangement above the base, and micro -structure array orientation and total reflection membrane goods length direction non - are perpendicular. The micro -structure be horizontal triangular prism, the triangular prism cross section is isosceles triangle, the horizontal section triangle base hand end portion of a